Inspection and evaluation of roofing systems: a case study - Santos, Lara Monalisa Alves dos; Andrade, Lucas Ferreira de; Pereira, Cláudio Henrique de Almeida Feitosa (Revista ALCONPAT, 2019)
The roof system of one of the buildings of the University of Brasília - DF is characterized and evaluated. The main existing anomalies in the roof systems are analyzed and the intervention priority is systematized, in order to correlate them with the corrective measures. The limiting factors for the inspection of the structures were accessibility as well as the lack of intervention projects. The results obtained reported that the main anomalies found in the systems are related to the lack of maintenance. The study also brings, as a contribution, indications and technical recommendations for the resolution of situations.